Strategi Peningkatan E-Business Untuk Meningkatkan Penjualan Internasional - Dina Aulia Nasution; Nurbaiti Nurbaiti (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
This research is conducted with the aim of gaining understanding and explaining how to develop e-business in international product marketing. Additionally, this research also aims to describe and analyze the tactical strategies applied to achieve success in e-business and product/service marketing. The research method used is qualitative research that focuses on the description and analysis of the implementation of e-business development in international product marketing. The data used are secondary data sourced from relevant journals on e-business enhancement strategies, especially at the international level.